Aplicativo Gross Motor Skills como suporte visual na avaliação do desempenho motor e implicações na motivação intrinseca na administração do Test of Gross Motor Development - third edition - Schardong, Ígor (2023)
Motor assessment of children presents numerous difficulties inherent to the process itself, among them the difference between the evaluators in the instruction and demonstration of motor skills. For administration of the Test of Gross Motor Development - Third Edition (TGMD-3) the evaluator must demonstrate to children the thirteen fundamental motor skills that make up the test. Different tools for visual support have been used to make the demonstration consistent, decreasing errors between evaluations and evaluators. Objective: To compare the motor performance and intrinsic motivation of children when evaluated with the TGMD-3 in two skills demonstration conditions, with visual support by animations of the Gross Motor Skills application and demonstration by the examiner. Materials and methods: This is a randomized crossover study with 134 children aged 3 to 10 years and 11 months, obtained by convenience from public and private schools in the state of Rio Grande do Sul. The children's motor performance was evaluated using the TGMD-3, with two protocols for demonstrating fundamental motor skills: traditional protocol (PTd), with the evaluator demonstrating, and application protocol (PApp) with the demonstration of skills by an animated character, using AppGMS. In the first evaluation, the children were randomly divided into two groups, half started with PTd and half with PApp. After seven days, the children were reassessed with inversion of protocols. At the end of each evaluation, the children answered the Intrinsic Motivation Inventory (IMI). Results: ANCOVA controlled by sex showed no effect of the protocol on the motor performance of locomotion skills (F1,267 = 0.415; p ≤ 0.52; η2 = 0.002), with ball (F1,267 = 0.024; p ≤ 0.89; η2 = 0.000) and total raw score (F1,267 = 0.170; p ≤ 0.68; η2 = 0.001) of the test, however it revealed that boys performed better than girls in ball skills (F1,267 = 14.98; p ≤ 0.01; η2 = 0.054) and total raw score (F1,267 = 9.50; p ≤ 0.01; η 2 = 0.035). As for locomotion skills, boys and girls showed the same performance (F1,267 = 1.34; p ≤ 0.25; η2 = 0.005). ANCOVA controls for age showed no effect of the protocol on the motor performance of locomotion skills (F1,267 = 0.099, p ≤ 0.75; η 2 = 0.000) with ball (F1,267 = 0.039; p ≤ 0.84; η2 = 0.001) and total raw score (F1,267 = 0.086; p ≤ 0.77; η2 = 0.000). There is an increase in children's motor performance with increasing age, with the exception of locomotion skills among children aged 6 to 8 years and 9 to 10 years. There was no difference between the protocols on the scale of Interest/Fun (p ≤ 0.75), Perceived competence (p ≤ 0.93), Effort/Importance (p ≤ 0.29) and Pressure/Tension (p ≤ 0.79). Conclusion: This study presents positive evidence for the use of the AppGMS as a visual support in the evaluation of motor performance with the TGMD-3, without prejudice to the children's motor performance scores and intrinsic motivation.